Statistical survey of the pathology, diagnosis and rehabilitation of ETICS in walls - Amaro, Bárbara; Saraiva, Diogo; Brito, Jorge de; Flores-Colen, Inês (Journal of Civil Engineering and Management, 2014)
This paper presents a statistical survey on the pathology, diagnosis and rehabilitation of ETICS (external thermal insulation composite system) in walls. The development of an expert-knowledge inspection and diagnosis system for this type of cladding implied the creation of classification lists of anomalies, most probable causes, diagnosis methods and repair/maintenance techniques. The collection of data through field work where the tools developed within the proposed system were applied was the basis for this statistical survey. The field work consisted of the visual inspection of 146 façades with ETICS cladding located in various areas in Portugal and aged from 3 to 22 years. The data obtained enable anomalies to be related to their causes and so conclusions can be drawn on the best way to minimize the development of the former and eliminate the latter, at the design and application stages. The study further revealed the main sensitive issues of the cladding system during its service life, highlighting the importance of a correct maintenance plan.